Perspektif Anatomi Dan Antropometri Pada Senyum - Wita Anggraini (Fakultas Kedokteran Gigi Universitas Trisakti, 2020)
The main muscle that forms a smile is the m.zygomaticus major, which pulls the corners of the mouth to the superior and lateral. The m.zygomaticus major area is related to one's appearance, both when active or inactive. Smiles are fundamentally divided into “spontaneous” or “true” smiles (